Cultural, Religious and Political Contestations: The Multicultural Challenge - Mansouri, Fethi (Springer, 2015)
This book examines the foundations of multiculturalism in the context of émigré societies and from a multi-dimensional perspective. The work considers the politics of multiculturalism and focuses on how the discourse of cultural rights and intercultural relations in western societies can and should be accounted for at a philosophical, as well as performative level. Theoretical perspectives on current debates about cultural diversity, religious minorities and minority rights emerge in this volume.